Blended learning in a Master’s Programme in Multimedia in Education: a critical view - Ramos, Fernando (2012)
In 2002, the University of Aveiro started a master’s programme in Multimedia in Education. Since then, this programme has grown to become one of the most successful post-graduation programmes of this University, with an average of more than 11 applicants for each available position and 5 editions in just 3 years. The main target audience for this programme are primary and secondary school teachers, although some higher education staff and professionals from multimedia editorial companies also apply. Having that in mind, the operational model adopted has some features selected to match the constraints of the target public, namely a sequential approach to courses and a blended learning strategy, heavily relying on eLearning technologies to help students and staff fulfil their tasks. This paper presents the main characteristics of the model adopted and discusses its strengths and weaknesses based on an evaluation study whose framework, parameters and methodology are also presented.